2008
DOI: 10.1620/tjem.215.237
|View full text |Cite
|
Sign up to set email alerts
|

Intervention Study of Exercise Program for Oral Function in Healthy Elderly People

Abstract: In Japan, one of the duties of the long-term care insurance system is the prevention of oral function degradation. Although various exercise programs for oral function have been developed and practiced in Japan, to date, no study has reported their effects. In the present study, we examined the effects of an exercise program on oral functions in healthy elderly people. Healthy elderly people participated in the study and were randomly divided into intervention and control groups (39 subjects/group). The exerci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
72
0
3

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(83 citation statements)
references
References 27 publications
2
72
0
3
Order By: Relevance
“…Oral function exercises have been developed in Japan for many years, and researchers in many studies in Japan have reported its effectiveness for improving oral function of older people . In addition, some studies have found that bite force as well as stimulated and non‐stimulated saliva secretion increased significantly after oral function exercise intervention . Kikutani et al found that oral function exercise intervention can increase the degree of nutrient absorption in the long‐term care of older people.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Oral function exercises have been developed in Japan for many years, and researchers in many studies in Japan have reported its effectiveness for improving oral function of older people . In addition, some studies have found that bite force as well as stimulated and non‐stimulated saliva secretion increased significantly after oral function exercise intervention . Kikutani et al found that oral function exercise intervention can increase the degree of nutrient absorption in the long‐term care of older people.…”
Section: Discussionmentioning
confidence: 99%
“…The oral health education programme employed various education materials for instruction, mainly regarding oral diseases common among older people, oral hygiene and oral function exercises. The oral function exercises comprised four physical exercises adapted from previous studies: verbal expression muscle exercises, tongue exercises, salivary gland massage, and swallowing and pronunciation exercises. The detailed procedures and effects of oral function exercises are described in Table …”
Section: Methodsmentioning
confidence: 99%
“…Aging is accompanied by a gradual physiological deterioration which drives to a reduction in daily activities. The oral functions are also affected, such as the salivary secretion, which results in xerostomia and tooth loss, influencing directly the strength of chewing and swallowing (16). Elderly living in nursing homes are the most vulnerable group to suffer from oral problems.…”
Section: Discussionmentioning
confidence: 99%
“…These results may indicate that subjective improvements had increased after 13 months and hence another set of interventions may be started and maintained within 24 months. In this study, we divided the intervention period into six months based on a previous study, which had reported improvements in bite force, RSST and salivary flow rate after a six‐month preventive care programme . However, no study has reported on the suitable intervention period for such analyses.…”
Section: Discussionmentioning
confidence: 99%